Hydrogeophysical model calibration and uncertainty analysis via full integration of PEST/PEST++ and COMSOL. (November 2021) - González-Quirós, Andrés; Comte, Jean-Christophe
Abstract: Calibration of groundwater models is frequently hampered by limited availability of hydrogeological data. Non-intrusive geophysical methods are increasingly used to provide higher spatio-temporal resolution datasets for identification of hydrological processes and estimation of hydraulic properties. In groundwater model calibration performed through joint or coupled hydrogeophysical inversion, the hydrogeological datasets are supplemented with auxiliary geophysical data. In this work we propose a methodological approach to perform coupled inversion by integrating the calibration software PEST/PEST++ with COMSOL Multiphysics using MATLAB. The strategy provides multiple options for calibration and uncertainty analysis relevant for a broad range of environmental models. To illustrate the approach, we show a hydrogeophysical application in which electrical resistivity is used jointly with borehole data for the identification of seawater intrusion in a coastal aquifer. Highlights: We present a strategy for hydrogeophysical inversion and uncertainty analysis. PEST/PEST++ and COMSOL Multiphysics are fully integrated. The approach is applied to electrical resistivity monitoring in a coastal aquifer. The coupled inversion achieves better delineation of seawater intrusion. Uncertainty analysis is done using PEST++ Iterative Ensemble Smoother.